The Dialectics of Stigma, Silence, and Misunderstanding in Suicidality Survival Narratives. Issue 8 (3rd August 2018) - Binnix, Taylor M.; Rambo, Carol; Abrutyn, Seth; Mueller, Anna S.
ABSTRACT: Modern suicidologists have noted a dearth of qualitative research on suicide. The first author conducted 20 in-depth interviews with formerly suicidal adults to understand how they accounted for their experiences contemplating or attempting suicide. According to participants, stigma necessitated impression management, which contributed to the production of silence and misunderstanding . Silence and misunderstanding reinforced stigma. This complex, dialectical, belief system about stigma yields insight into the interpretive culture of surviving suicidal ideation or a suicide attempt. These beliefs about suicide may serve as a barrier to individuals seeking help, recovering from suicidality, and larger social change regarding attitudes toward suicide.